Evolución y modelos de implementación de sistemas de gestión de continuidad del negocio (2021)
The business continuity management system (BCMS) is a tool that allows organizations to prepare for scenarios affecting their normal functioning. In this process, an impact assessment and risk assessment is required, identifying, establishing and evaluating business continuity plans (BCP) to ensure resources and necessary personnel availability. In this article the evolution, BCM implementation models, and associated risk management strategies are addressed. Thirty-seven (37) articles related to BCM are analized concluding that BCM evolution has allowed organizations to access models that facilitate the system implementation, according to the needs, availability of resources, personnel competence and with a PHVA approach (plan, do, check and act).